Objectifying Micrognathia Using Three-Dimensional Photogrammetric Analysis. Issue 8 (November 2018) - Basart, Hanneke; Suttie, Michael; Ibrahim, Amel; Ferretti, Patrizia; van der Horst, Chantal M.A.M.; Hennekam, Raoul C.; Hammond, Peter
Abstract : Background: Micrognathia occurs isolated and as part of entities like Robin sequence (RS). An objective measurement of mandible size and growth is needed to determine the degree of micrognathia and enable a comparison of treatment outcomes. A pilot study was conducted to investigate the usability of 3-dimensional (3D) facial photogrammetry, a fast, noninvasive method, to estimate mandible size and growth in a small cohort of newborns and infants. Methods: Exterior mandibular volume was estimated using a tetrahedron defined by 4 facial landmarks. Twelve patients with RS with different etiologies were selected and photogrammetric images were obtained prospectively in 3 patients with RS in whom mandibular growth in the first year of life was determined. We used 3 tetrahedra defined by 6 landmarks on mandibular computed tomography (CT) scans to estimate an interior mandibular volume, which we compared to the exterior mandibular volume in 10 patients. Results: The exterior mandibular volume using 3D photography could be determined in all patients. Signature heat maps allowed visualization of facial dysmorphism in 3D; signature graphs demonstrated similarities of facial dysmorphism in patients with the same etiology and differences from those with other diagnoses and from controls. The correlation between interior (3D photogrammetry) and exterior mandibular volumes (CT imaging) was 0.8789. Conclusion: The 3D facial photogrammetry delineates the general facial characteristics in patients with different syndromes involving micrognathia, and can objectively estimate mandibular volume and growth, with excellent correlation with bony measurement. It has been concluded that 3D facial photogrammetry could be a clinically effective instrument for delineating and quantifying micrognathia.